PERLINDUNGAN HUKUM ISLAM TERHADAP JANIN - Idrus, Achmad Musyahid (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2015)
Janin or fetus is one of the real problem in Islamic law sincelong time ago till today. There are many problems that caused janin or fetus aborsed by mothers and the most important of this problems is the unpragnancy. Islamic law stressed that janin or fetus must be respected by all humans so that Islamic law encouranges mothers and father to protect the janin or fetus in their mother’s uterus. That why, janin or fetus actually has life and has potentially to grow up in many cells to be human.